2009
DOI: 10.1088/0957-0233/20/12/125404
|View full text |Cite
|
Sign up to set email alerts
|

An approximate formula for the capacitance–void fraction relationship for annular flows

Abstract: A capacitance method is applied to measure the space-averaged void fraction in concentric annular flows. From the analytical solution of the governing electrical field equations, the expression for the capacitance in terms of a given void fraction is derived. Also, a closed form formula to predict the void fraction from the capacitance measurement is proposed. The relationship between the capacitance and the void fraction is successfully compared with static phantom experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The correlations (Srisomba et al [9]) are different for the three flow patterns above. Kim et al [10] proposed a capacitance method to measure the space-averaged void fraction in concentric annular flows, derived the expression for the capacitance in terms of a given void fraction, and developed a closed-form formula to predict the void fraction from capacitance measurements. Uesawa et al [11] proposed a void fraction estimation method for three-dimensional dispersed bubbly flow based on Maxwell's theory and polarization of tiny bubbles whereas Jassim and Newell [12] developed probabilistic two-phase flow map models to predict void fraction and pressure drop for R134a, R410A and air-water in 6-port microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…The correlations (Srisomba et al [9]) are different for the three flow patterns above. Kim et al [10] proposed a capacitance method to measure the space-averaged void fraction in concentric annular flows, derived the expression for the capacitance in terms of a given void fraction, and developed a closed-form formula to predict the void fraction from capacitance measurements. Uesawa et al [11] proposed a void fraction estimation method for three-dimensional dispersed bubbly flow based on Maxwell's theory and polarization of tiny bubbles whereas Jassim and Newell [12] developed probabilistic two-phase flow map models to predict void fraction and pressure drop for R134a, R410A and air-water in 6-port microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…Shu et al (1982) derived a solution to the Laplace equation for the concentric annular geometry in a plate-type capacitance sensor, and conducted sensitivity analyses with respect to the thickness of the dielectric pipe. Kim et al (2009b) developed a closed-form of expression suggesting a relationship between the normalized capacitance and the void fraction in the concentric annular flow. Tsochatzidis et al (1992) derived a conductance response to stratified and annular flow in ring sensor geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Tsochatzidis et al (1992) derived a conductance response to stratified and annular flow in ring sensor geometry. Also, Kim et al (2009b) suggested an expression of the conductance response to slug flow in a three-ring sensor in a simplified manner and compared it with experiments using an acryl rod simulating a Taylor bubble.…”
Section: Introductionmentioning
confidence: 99%